1988
DOI: 10.1073/pnas.85.21.8086
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression in the embryonic nervous system of Xenopus laevis.

Abstract: Development of the nervous system in the amphibian embryo is initiated during gastrulation by an inductive interaction between chordamesoderm and dorsal ectoderm. The induced ectoderm forms the neural plate while uninduced ectoderm generates epidermis. We screened for genes activated during gastrulation and expressed specifically in the nervous system of Xenopus laevis in the expectation that clones representing such genes will constitute useful markers for the study of early neurogenesis. Probes were prepared… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
74
0

Year Published

1991
1991
2014
2014

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 151 publications
(74 citation statements)
references
References 59 publications
(47 reference statements)
0
74
0
Order By: Relevance
“…The near full-length a, cDNA (-45 to +3349 bp = &wt) from Xcnopus laevis previously cloned from an A6 kidney cell library [9] and a /3x cDNA cloned from a Xenopus neurula library [7,8] were inserted into the pSDS vector [6]. We have previously shown that both the PI September 1991 Fig.…”
Section: Deletion Mutnnl At the N Terminus Of The ~1 Isofarmmentioning
confidence: 99%
“…The near full-length a, cDNA (-45 to +3349 bp = &wt) from Xcnopus laevis previously cloned from an A6 kidney cell library [9] and a /3x cDNA cloned from a Xenopus neurula library [7,8] were inserted into the pSDS vector [6]. We have previously shown that both the PI September 1991 Fig.…”
Section: Deletion Mutnnl At the N Terminus Of The ~1 Isofarmmentioning
confidence: 99%
“…17. Antisense probes labeled with digoxigenin were synthesized by using cDNA templates encoding Zic3 (18), Xbra (19), N-tubulin (20), and En2 (21). For xPRMT1b ISH, we used the fragment 3E10, located in the 3ЈUTR of xPRMT1b.…”
Section: Methodsmentioning
confidence: 99%
“…Plasmids containing N-tubulin (Richter et al, 1988), Xenopus Krox-20 (Bradley et al, 1993), Xenopus Ap-2 (Winning et al, 1991), Xenopus Slug (Mayor et al, 1995), Xenopus Zic3 (Nakata et al, 1997), and Xenopus type I keratin (Miyatani et al, 1986) were linearized with restriction enzymes (StuI for N-tubulin, EcoRI for XKrox-20, HindIII for Xap-2, EcoRI for XSlug, BamHI for XZic3, and EcoRI for Xkeratin), and digoxygenin-labeled riboprobes were synthesized using T3 (for N-tubulinand XZic3) or T7 (for XKrox-20, Xap-2, and XSlug) or SP6 (for Xkeratin) polymerase. Wholemount in situ hybridization was essentially done as described by Harland (1991).…”
Section: Whole-mount In Situ Hybridizationmentioning
confidence: 99%